Questions for future evidence-informed policy initiatives: insights from the evolution and aspirations of National Immunization Technical Advisory Groups - Anne L. Buffardi; Susan Njambi-Szlapka (BMC, 2020)
Abstract Background Attention to evidence-informed policy has grown; however, efforts to strengthen the quality and use of evidence are not starting from a blank slate. Changes in health architectures and financing pose different considerations for investments in evidence-informed policy than in the past. We identify major trends that have shifted the environment in which health policies are made, and use the evolution and future aspirations of National Immunization Technical Advisory Groups (NITAGs) in low- and middle-income countries to identify questions the sector must confront when determining how best to structure and strengthen evidence-informed health policy. Discussion Trends over the last two decades have resulted in a dense arena with many issue-specific groups, discrete initiatives to strengthen evidence-informed policy and increasing responsibility for subnational institutions. Many countries face a shifting resource base, which for some reduces the amount of resources for health. There is global momentum around universal health coverage, reflecting a broader systems approach, but few examples of how the vast array of stakeholders relate within it are available. NITAG aspirations reflect four interconnected themes related to their scope, their integration in national policy processes, health financing and relationships with ministries of finance, and NITAG positioning relative to other domestic and international entities, raising questions such as, What are the bounds of issue-specific groups and their relationship to allocation decision-making processes across health areas? How do technical advisory groups interface with what are inherently political processes? When are finances considered, by whom and how? What is the future of existing groups whose creation was intended to enhance national ownership but who need continued external support to function? When should new entities be created, in what form and with what mandate? Conclusions Countries must determine who makes decisions about resources, when, using what criteria, and how to do so in a robust yet efficient way given the existing and future landscape. While answers to these questions are necessarily country specific, they are collective matters that cannot be addressed by specialised groups alone and have implications for new investments in evidence-informed policy.